2020
DOI: 10.1093/zoolinnean/zlaa019
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Trojan horse: phylogeny of Astyanax, two new genera and resurrection of Psalidodon (Teleostei: Characidae)

Abstract: The freshwater fish genus Astyanax is one of the most diverse among the Characidae. The genus is defined by a combination of character states that are widely distributed in Characidae. In addition, the genus has the broadest geographical distribution in the family, being found in a great variety of environments of the Neotropical region. Although phylogenetic relationships were treated only partially, many authors agree that the genus is not monophyletic. In this contribution, we study the phylogenetic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 74 publications
2
64
0
8
Order By: Relevance
“…This two genera have been discussed in a recent taxonomic study. The taxonomic status of three species has been reassessed: Hemigrammus bleheri should be Petitella bleheri ( Bittencourt et al, 2020 ), renamed Astyanax giton as Deuterodon giton , and Astyanax paranae as Psalidodon paranae ( Terán et al, 2020 ). These results indicated that the taxonomic status of the family Characidae is currently unresolved, and morphological classification combined with the usage of mitogenomes and other molecular markers are needed for comprehensive classification ( Liu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This two genera have been discussed in a recent taxonomic study. The taxonomic status of three species has been reassessed: Hemigrammus bleheri should be Petitella bleheri ( Bittencourt et al, 2020 ), renamed Astyanax giton as Deuterodon giton , and Astyanax paranae as Psalidodon paranae ( Terán et al, 2020 ). These results indicated that the taxonomic status of the family Characidae is currently unresolved, and morphological classification combined with the usage of mitogenomes and other molecular markers are needed for comprehensive classification ( Liu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Omnivory in Neotropical streams is mainly represented by small fish species from the family Characidae. Among these, Psalidodon and Astyanax are highly diverse genera with a wide geographical distribution (Eschmeyer et al 2016;Rossini et al 2016;Bonato et al 2017;Silva et al 2017;Terán et al 2020). Although species of these genera are considered to be omnivores (Baumgartner et al 2012), responses in their feeding and resource assimilation to seasonal changes are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the Iguaçu river basin (Brazil), there are 12 species of the genera Astyanax and Psalidodon (Haluch and Abilhoa 2005;Abilhoa and Duboc 2007;Pavanelli and Oliveira 2009;Baumgartner et al 2012;Ingenito and Duboc 2014); with Psalidodon bifasciatus (Garavello and Sampaio 2010) and Psalidodon gymnodontus (Eigenmann 1911) among the most common and dominant species (Baumgartner et al 2012;Neves et al 2015;Larentis et al 2016;Delariva et al 2018;Baldasso et al 2019). These species were recently relocated to the genus Psalidodon by Terán et al (2020), previously being recognized as Astyanax gymnodontus and Astyanax bifasciatus. This basin has a high number of endemic tetra fish species but the overall diversity of fish fauna is low in comparison with other basins (Zawadzki et al 1999;Baumgartner et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Psalidodon species were recently relocated to the genus Psalidodon by Terán et al. (2020), and until then, they were recognized as Astyanax aff. gymnodontus , Astyanax aff.…”
Section: Methodsmentioning
confidence: 99%